2017
DOI: 10.1038/s41598-017-03285-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human plasma phospholipid transfer protein (PLTP) to prevent bacterial growth and to treat sepsis

Abstract: Although plasma phospholipid transfer protein (PLTP) has been mainly studied in the context of atherosclerosis, it shares homology with proteins involved in innate immunity. Here, we produced active recombinant human PLTP (rhPLTP) in the milk of new lines of transgenic rabbits. We successfully used rhPLTP as an exogenous therapeutic protein to treat endotoxemia and sepsis. In mouse models with injections of purified lipopolysaccharides or with polymicrobial infection, we demonstrated that rhPLTP prevented bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…Upon infection, lung protease activity is elevated and proteins required for microbial clearance and normal lung function are subjected to enhanced degradation 41 . This is further relevant to this study, as PLTP prevents bacterial growth observed in sepsis 42 and PLTP activity has a strong correlation with lung function in COPD subjects 15 . Here, we show that the PiZZ form of AAT is less efficient at preventing PLTP cleavage than the PiMM form and PLTP has important anti-inflammatory properties against neutrophils from both AAT deficient and competent individuals.…”
Section: Discussionmentioning
confidence: 78%
“…Upon infection, lung protease activity is elevated and proteins required for microbial clearance and normal lung function are subjected to enhanced degradation 41 . This is further relevant to this study, as PLTP prevents bacterial growth observed in sepsis 42 and PLTP activity has a strong correlation with lung function in COPD subjects 15 . Here, we show that the PiZZ form of AAT is less efficient at preventing PLTP cleavage than the PiMM form and PLTP has important anti-inflammatory properties against neutrophils from both AAT deficient and competent individuals.…”
Section: Discussionmentioning
confidence: 78%
“…On the contrary, increased PLTP lipid transfer activity has earlier been measured in both acute and chronic inflammations [49][50][51]. It has also been shown that PLTP can protect mice from lethal endotoxemia [52] independently of the HDL pool [53] by neutralizing LPS and preventing the growth of gram-negative bacteria [54]. Jänis and co-workers been proposed that PLTP has two forms regarding the lipid transfer activity, an active and an inactive [55].…”
Section: Discussionmentioning
confidence: 99%
“…This specific function displayed by PLTP allows scavenging of LPS from the circulation to biliary secretion and has been called the “reverse LPS transport.” It has been demonstrated in vitro a lower production of pro-inflammatory cytokines in LPS-stimulated splenocytes from wild-type (WT) mice compared to those of splenocytes from PLTP-deficient (PLTP −/− ) mice in the presence of lipoproteins as “LPS-carrier.” This experiment sustained the role of PLTP in LPS metabolism. The “reverse LPS transport” was also addressed in the context of endotoxin shock, and more recently in the setting of sepsis: PLTP −/− mice exhibited a significant higher mortality rate than WT mice ( 17 , 20 ). Thus, proteins from the LT/LBP family should be considered in the GVHD pathophysiology.…”
Section: Innovative Insights On Lps To Reconsider “Former” Datamentioning
confidence: 99%